Primary prostatic signet ring cell carcinoma in elderly with obstructive uropathy: a case report - Simran Kaur Sidhu; Mohamad Fairuz Mohd Sharin; Khairul Asri Mohd Ghani; Saiful Azli Mohd Zainuddin; Nornazirah Azizan; Mohd Firdaus Mohd Hayati (Springer, 2022)
Background: Primary signet-ring cell carcinoma (SRCC) of the prostate is a rare and aggressive subtype of prostate adenocarcinoma with a poor prognosis, with only approximately 60 cases reported worldwide. Case presentation: A 62-year-old man presented with acute urinary retention and hematuria, after a year’s history of lower urinary tract symptoms. Digital rectal examination revealed an irregular and hard prostate. Flexible cystoscopy showed bladder base infiltration by the enlarged prostate obscuring both ureteric orifices, necessitating nephrostomy and subsequent bilateral antegrade stenting to relieve the obstruction and improve his renal function. Transrectal ultrasonography biopsy of the prostate was performed revealing histological features of SRCC. Due to its rarity, there is currently no standardized treatment approach and it is often similarly treated according to the traditional management of prostate adenocarcinoma. Conclusions: SRCC of the prostate is a rare and aggressive subtype of acinar adenocarcinoma with no established guidelines. Histological criteria for SRCC of the prostate are highly variable in the available literature. It is important to differentiate between the primary and metastatic SRCC of the prostate as both are managed differently. However, the overall prognosis remains poor in general.